2020
DOI: 10.1146/annurev-physiol-021119-034618
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Polyploidy and Implications for Heart Regeneration

Abstract: In mammals, most cardiomyocytes (CMs) become polyploid (they have more than two complete sets of chromosomes). The purpose of this review is to evaluate assumptions about CM ploidy that are commonly discussed, even if not experimentally demonstrated, and to highlight key issues that are still to be resolved. Topics discussed here include ( a) technical and conceptual difficulties in defining a polyploid CM, ( b) the candidate role of reactive oxygen as a proximal trigger for the onset of polyploidy, ( c) the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 79 publications
0
52
0
2
Order By: Relevance
“…59 Recent studies conclude that the mononucleated diploid cardiomyocyte appears to be the primary cardiomyocyte subpopulation that is capable of proliferation and of supporting regeneration, which provides a reliable parameter for determining the proliferation and generation of cardiomyocytes. 27,29,61 Thus, the significantly increased ratio of EdU-positive mononucleated diploid cardiomyocytes in Lrp6-CKO mice suggested the cytokinesis and proliferation of cardiomyocyte induced by LRP6 deficiency.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…59 Recent studies conclude that the mononucleated diploid cardiomyocyte appears to be the primary cardiomyocyte subpopulation that is capable of proliferation and of supporting regeneration, which provides a reliable parameter for determining the proliferation and generation of cardiomyocytes. 27,29,61 Thus, the significantly increased ratio of EdU-positive mononucleated diploid cardiomyocytes in Lrp6-CKO mice suggested the cytokinesis and proliferation of cardiomyocyte induced by LRP6 deficiency.…”
Section: Discussionmentioning
confidence: 96%
“…4f). Considering that the diploid cardiomyocyte just appears to be the primary cardiomyocyte subpopulation that is capable of proliferation and of supporting regeneration, 29 these data suggested that the increase in mononuclear diploid cardiomyocyte rather than polyploidization, may account for the cardiac regeneration mediated by LRP6 deficiency.…”
Section: Lrp6 Deficiency Increases Neonatal Rat Cardiomyocyte Prolifementioning
confidence: 94%
“…Unfortunately, mammalian CMs typically lose proliferation capacity early after birth due to (permanent) cell cycle arrest. (101,102,(179)(180)(181) The cell cycle is tightly regulated by transcription factors, cyclins and cyclin-dependent kinases (CDKs) as well as upstream regulators including the pocket proteins (i.e., pRb/p105, pRb1/p107 and pRb2/p130), CDK inhibitors of the CIP/KIP and INK4 families and the tumor suppressor protein p53 (182)(183)(184). The identification and ectopic expression of viral oncogenes made it possible to "immortalize" post-mitotic cells resulting in their cell cycle reentry and subsequent proliferation (185).…”
Section: Immortalized Amsmentioning
confidence: 99%
“…In mammals, only a small percentage of adult ventricular cardiomyocytes (CMs) are diploid (i.e., have a single 2n nucleus (n is the haploid chromosomal content), also called mononuclear diploid or abbreviated as 1 × 2n) (reviewed in 1,2 ). Through a process known as endoreplication, CMs enter cell cycle and progress through S-phase DNA replication, but then fail to complete mitosis.…”
mentioning
confidence: 99%